Metabolism of Scoparone in Experimental Animals and Humans - Juvonen, Risto O.; Novák, Filip; Emmanouilidou, Eleni; Auriola, Seppo; Timonen, Juri; Heikkinen, Aki T.; Küblbeck, Jenni; Finel, Moshe; Raunio, Hannu (Planta Medica, 2019)
Scoparone, a major constituent of the Chinese herbal medicine Yin Chen Hao, expresses beneficial effects in experimental models of various diseases. The intrinsic doses and effects of scoparone are dependent on its metabolism, both in humans and animals. We evaluated in detail the metabolism of scoparone in human, mouse, rat, pig, dog, and rabbit liver microsomes in vitro and in humans in vivo. Oxidation of scoparone to isoscopoletin via 6-O-demethylation was the major metabolic pathway in liver microsomes from humans, mouse, rat, pig and dog, whereas 7-O-demethylation to scopoletin was the main reaction in rabbit. The scoparone oxidation rates in liver microsomes were 0.8 – 1.2 µmol/(min*g protein) in mouse, pig, and rabbit, 0.2 – 0.4 µmol/(min*g protein) in man and dog, and less than 0.1 µmol/(min*g) in rat. In liver microsomes of all species, isoscopoletin was oxidized to 3-[4-methoxy-ρ-(3, 6)-benzoquinone]-2-propenoate and esculetin, which was formed also in the oxidation of scopoletin. Human CYP2A13 exhibited the highest rate of isoscopoletin and scopoletin oxidation, followed by CYP1A1 and CYP1A2. Glucuronidation of isoscopoletin and scopoletin was catalyzed by the human UGT1A1, UGT1A6, UGT1A7, UGT1A8, UGT1A9, UGT1A10, and UGT2B17. Dog was most similar to man in scoparone metabolism. Isoscopoletin glucuronide and sulfate conjugates were the major scoparone in vivo metabolites in humans, and they were completely excreted within 24 h in urine. Scoparone and its metabolites did not activate key nuclear receptors regulating CYP and UGT enzymes. These results outline comprehensively the metabolic pathways of scoparone in man and key preclinical animal species.
Keywords: scoparone; isoscopoletin; scopoletin; esculetin; CYP; UGT